La-supported SnO2–CaO composite catalysts for efficient malachite green degradation under UV–vis light - Nastaran Parsafard; Ghazaleh Aghajari (BMC Chemistry)
Abstract This study presents the development and optimization of La@SnO2–CaO composite catalysts for efficient photocatalytic degradation of malachite green dye in aqueous solutions under UV–vis light irradiation. The catalysts were prepared via conventional incipient-wetness impregnation and thoroughly characterized using advanced analytical techniques, including X-ray diffraction, Fourier transform infrared spectroscopy, UV–vis diffuse reflectance spectroscopy, N2 adsorption–desorption analysis, and scanning electron microscopy. To optimize photodegradation efficiency, the effects of three independent factors were systematically investigated using response surface methodology: Temperature, pH, and Sn/Ca molar ratio. Our results reveal optimal conditions for maximum dye degradation: pH 7, Sn/Ca molar ratio of 0.33, and a process time of 35 min, resulting in a maximum photodegradation efficiency of 98.80% for malachite green dye. Notably, visible light exhibited a more pronounced effect on dye degradation compared to UV light over time, with visible light achieving 25% greater dye removal after 60 min of illumination. Furthermore, the catalyst showed excellent recyclability, retaining 85% of its initial activity after five consecutive cycles. These findings contribute significantly to the development of sustainable methods for dye removal from wastewater and highlight the potential of La@SnO2–CaO composite catalysts in environmental remediation processes, particularly in treating textile industry effluents.